Circulating proinflammatory cytokines (IL‐1β, TNF‐α, and IL‐6) and IL‐1 receptor antagonist (IL‐1Ra) in fulminant hepatic failure and acute hepatitis - SEKIYAMA, K. D.; YOSHIBA, M.; THOMSON, A. W. (Clinical and experimental immunology, 1994)
SUMMARY Fulminant hepatic failure (FHF) is characterized by massive necroinflammation of the liver tissue and is associated with high mortality. Serum concentrations of IL‐1β, tumour necrosis factor‐a (TNF‐α). IL‐6 and IL‐I receptor antagonist (IL‐IRa) were measured in 30 patients with FHF and in 23 patients with acute hepatitis (AH) before start of treatment and in 23 healthy controls. Levels of all four molecules were increased significantly in FHF compared with AH, in which values were higher than in the healthy controls. High serum levels of IL‐1β and a significantly reduced ratio of IL‐IRa to IL‐Iβ (IL‐lRa/IL‐lβ) were observed in FHF patients who subsequently died compared with subjects who survived. TNF‐α and IL‐6 concentrations were correlated with levels of human hepatocyte growth factor (hHGF), an index of hepatocyte regeneration. Although serum cytokine levels varied considerably between patients within each group studied, it is suggested that the striking elevation in proinflammatory cytokine levels in FHF may reflect both the insufficiency of hepatitis virus elimination and a failure to control a vicious cytokine cascade leading to overwhelming hepatocyte destruction rather than regeneration. The high cytokine levels observed in these patients and the significantly elevated IL‐IRa/IL‐lβ ratio in FHF patients who survived compared with those who did not suggest the possible therapeutic use of cytokine antagonists for the control of this life‐threatening disease.